The Influence of Mother Tongue on Indonesian Language Learning in Grade VII at UPT SMP Negeri 4 Baranti - Musdalifa Basri; Nuraini Kasma; Nurlaelah Mahmud; Muhammad Hanafi (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study aims to identify and measure the influence of mother tongue use on Indonesian language learning outcomes among Grade VII students at UPT SMP Negeri 4 Baranti. The research employed a quantitative method with a true-experimental posttest-only control design. The sample consisted of 40 students, divided into two groups: 20 students in the experimental group who received instruction integrating the mother tongue (Bugis language) and 20 students in the control group who learned conventionally using Indonesian. Data collection techniques included multiple-choice tests (posttest) and questionnaires. The results showed a significant difference between the two groups. The experimental group achieved a higher average learning outcome score compared to the control group. Data analysis using the independent sample t-test yielded a significance value of 0.008 (p < 0.05) and an average score difference of 10.9, indicating that H₀ was rejected and H₁ was accepted. This proves there is a significant difference between the two groups. Furthermore, the questionnaire results also revealed positive student responses toward the use of the mother tongue in the learning process. In conclusion, the use of the mother tongue has been proven to have a significant positive effect on improving Indonesian language learning outcomes for Grade VII students at UPT SMP Negeri 4 Baranti.